Angiopteris involuta (Marattiaceae), a new endangered fern species from southern Yunnan, China, based on morphology and molecular evidence - Jiang, Li-Ju; Zhao, Jing; Niu, Hong-Bin; Zhou, Xin-Mao; Wang, Jia-Guan; He, Zhao-Rong (Phytotaxa, 2025)
A new fern species, Angiopteris involuta L.J. Jiang & Z.R. He, is described from southern Yunnan, China. This taxon exhibits intermediate morphology between Angiopteris s.s. and Archangiopteris, characterized by its ascending rhizome, once pinnate to bipinnate, involute fertile pinnules, and long-linear, medial sori. Molecular phylogenetic analysis based on plastome data indicates that A. involuta is closely related to species of Archangiopteris s.s. (A. bipinnata, A. chingii, A. latipinna, and A. nodosipetiolata), but distinct from other intermediate species belonging to Angiopteris s.s. (A. itoi, A. sparsisora, and A. sugongii). The species is assessed as Critically Endangered (CR) under IUCN criteria due to habitat loss and its extremely limited distribution.